Prenatal morphogenic and histogenic development of the kidney in rabbits (Oryctolagus cuniculus) - Mohamed Aref; Noha Ali Abd-Almotaleb; Eman H. Elsheikh; Gamal A. Salem; Mohamed A. Nassan; Esraa Elsheikh (Open Veterinary Journal)
Background: Rabbits are easily available and docile animals; thus, they are a promising model for medical research. White New Zealand rabbits are usually employed for research.